The Age and Provenance of the Globidens timorensis Holotype - Maayke J. Koevoets; Anne S. Schulp; Simon R. Troelstra (Berita Sedimentologi, 2014)
Three fossil teeth reported from the Upper Cretaceous of West Timor are the only known fossils of Mosasaurus-type marine reptiles in the eastern Tethys region. However, there is some uncertainty about the exact locality of origin of these fossils.